Environmental Impact Assessment in the context of armed conflicts - Urban, Sergiusz (The Opole Studies in Administration and Law, 2023)
The Environmental Impact Assessment (EIA) is a legal, procedural tool that allows to identify, predict, evaluate and prevent or mitigate the impacts of a planned project on the environment. An inherent element of this process is public participation that shall be assured at all times. EIA is regulated by domestic environmental laws of a given county, but an imminent influence on these regulations is exerted by EU EIA Directive (Directive 2011/92/EU text codified) and international conventions, especially the ESPOO Convention. EU legislation and international EIA-focused treaties do not determine if armed conflicts affect the EIA procedures and, if the answer is positive, in which way, especially whether the EIA procedure remains required under these exceptional circumstances or it may be postponed until cease of conflict or even omitted. For this reason, it was of high importance to determine whether EIA-related obligations set by EU and international laws are suspended or remain valid and in force during armed conflicts. The research revealed that the above-mentioned acts do not have provisions that explicitly regulate the effect of armed conflicts on the obligations relating to the EIA procedures. Furthermore, current jurisprudence and doctrine do not provide clear answer on the scope of application of international environmental law during armed conflict. It is often explained by the fact that environmental law is not yet fully formed in that respect and it is still not commonly agreed how it relates to international humanitarian law. Based on findings of the research, some conclusions are proposed that aim at providing advise on the application of EIA during armed conflicts and suggestions to supplement discussed bodies of law. This article will discuss the main results of the study conducted on this important and very up-to-date subject.